Índice de refração na teoria gravitacional de Brans-Dicke : um estudo para métricas estáticas e pressões não nulas - Antonio Francisco Leitão (2009)
In this work we obtain the refractive index taking the Brans-Dicke theory as the fundamental and underlying gravitational theory. In our investigation we consider that the spacetime is static and we makes no assumptions about the relative smallness or isotropy of internal pressures of the sources generating the gravitational field. We employ the technique of weaking the gravitational field equations in order to derive formulae for the refractive index tensor and we make some applications of these results